ВПЛИВ БЛОКАДИ Ш-СИНТАЗИ НА ВАЗОДИЛАТАЦІЙНИЙ ЕФЕКТ ДІЕТИЛОВОГО ЕСТЕРУ 5-АЛКІЛАМІНО-2-{М-[М-БЕНЗОЇЛ-(4-МЕТИЛБЕНЗИЛІДЕН) ГЛІЦИЛ] АМІНОМЕТИЛ}-1,3-ОКСАЗОЛ-4-ІЛФОСФОНОВОЇ КИСЛОТИ НА СЕГМЕНТАХ ІЗОЛЬОВАНОЇ АОРТИ ЩУРІВ - Nizhenkovska, І. V.; Romanenko, O. V.; Sedko, K. V.; Grusha, M. M.; Brovarets, V. S.; Holovchenko, O. V. (Фармацевтичний часопис, 2016)
INFLUENCE OF NO - SYNTHASE BLOCKADE ON VASODILATORY EFFECT OF DIETHYL ESTER OF 5-ALKILAMINE-2-{N-[N-BENZOYL-(4-METHYLBENZILIDEN) GLYCYL] AMINOMETHYL}- 1,3 - OXASOL-4-YLPHOSPHONIC ACID ON RAT’S ISOLATED AORTA I.V. Nizhenkovska1, A.V. Romanenko1, K.V. Sedko1, M.М. Grusha1, V.S. Brovarets2, A.V. Golovchenko2 1 Bogomolets National Medical University 2 Institute of Bioorganic Chemistry and Petrochemistry at NAS of Ukraine Essential hypertension, hypertensive heart disease, secondary hypertension and related diseases caused by them are the result of a lot of pathological changes in the cardiovascular system. One of the main mechanisms which affects the blood pressure is increasing of the tone of smooth muscle vascular wall component. A significant number of endogenous vasodilators exert their activity by mechanisms which are directly or indirectly related to the production of nitric oxide by endothelial cells, so the effects associated with its release, is a target for pharmacological correction of muscle tone in clinical practice. Previously, it was found that phosphorylated peptidomimetics, which are derivatives of 1,3-oxazole, have vasodilatative effects. However, the contribution of mechanisms of NO production and its release on vasotropic action of these compounds was not researched. That`s why the aim of our experiment was to study the vasodilatative effects of new synthesized derivative of 1,3-oxazole - diethyl ester of 5-alkilamine-2-{N-[N-benzoyl-(4-methylbenziliden) glycyl] aminomethyl}- 1,3 - oxasol-4-ylphosphonic acid (oxazole containing peptidomimetic) on rat’s isolated aorta on the background of the NO-synthase blockade. For experiment it was used isolated segments (n=5) of the thoracic descending aorta of Wistar rats with average weight 200-250 g. Received aortic segments before the experiment were kept at least 30 minutes at a temperature 35-37 °C in Krebs solution. To register the tone of aortic segments it was used installation consisting of a flow chamber (volume - 2 ml) at 36,5 °C. Vasodilatative activity of the compound was estimated by the effect on basal tone and amplitude of smooth muscle contraction of blood vessels in response to the including of α1-adrenoreceptor agonist -adrenalin (5•10-6 M) in the incubation medium. In assessing the effectiveness of vasoactive impact of the researched substance as 100% was taken the amplitude of tonic contraction of muscle in control in response to adrenaline (5•10-6 M) application for 10 sec. Average amplitude of adrenoreaction in control was 3,34 ± 1,07 mN. Adding of NO-synthase blocker - L-NAME (1•10-4 M) to Krebs solution had not an effect on basal tone of smooth muscles isolated segment of the thoracic descending aorta. However, the adding of L-NAME (1•10-4 M) to perfusate caused increasing the amplitude of adrenoreaction on 71% from baseline on 90th minute. The received changes in the amplitude are probably related to the blockade by L-NAME of NO production and release, and reducing the effect of vasodilatative component in providing the vascular reactivity to the action of α1-adrenergic receptors agonist - adrenaline (5•10-6 M). Additional including of oxazole containing peptidomimetic (1•10-5 M) to perfusate, after 30 minutes from beginning of application caused the amplitude reduction of adrenoreaction by 33% comparatively with its amplitude in conditions of only L-NAME (1•10-4 M) presence in the perfusate. The effect, which was caused by the including of oxazole containing peptidomimetic (1•10-5 M) to Krebs solution, was reversible. Within 30 min after removing of the last substance of perfusate, amplitude of adrenoreaction increased by 26% comparatively with its amplitude in conditions of simultaneous presence both of these compounds in solution. L-NAME removing of Krebs solution lead to regular amplitude decreasing of adrenoreaction. Experiments, conducted by using isolated segments of the rat`s thoracic descending aorta give reason to consider that diethyl ester of 5-alkilamine-2-{N-[N-benzoyl-(4-methylbenziliden) glycyl] aminomethyl}- 1,3 - oxasol-4-ylphosphonic acid (1•10-5 M) is able to keep its vasodilatative properties in conditions of NO-synthase blockade. The fact of saving of oxazole containing peptidomimetic effective action on the background of NO-synthase blockade by L-NAME (1•10-4 M) shows that vasodilatative effect of these two compounds is realized through various targets. Therefore, further study of vasodilatative mechanism of test compound, which can be used as potential antihypertensive medicine, is perspective for next researches. Literature: International Classification of Diseases 10th revision [Electron resource]. - Access: httpHYPERLINK "http://mkb-10.com/"://HYPERLINK "http://mkb-10.com/"mkbHYPERLINK "http://mkb-10.com/"-10.HYPERLINK "http://mkb-10.com/"comHYPERLINK "http://mkb-10.com/"/. Nizhenkovskaya I.V. The influence of sufan on myocardial energetic metabolism in case of adriamycin-induced heart failure. / Nizhenkovskaya I.V. // Research Trends. Current Topics in Pharmacology. Short Communication. SCOPUS. – 2013. - 17, 1. – P. 103-108. Mishichnie tkani: uchebnoe posobie dlya vuzov / U.S. Chentsov, Е.А. Shubnicova, N.А. Yurina, N.B. Gusev. - М.: Medicina, 2001. - 256 s. Ryabov G.А. Rol` oxida azota kak regulyatora kletochnih protsessov pri formirovanii poliorgannoy nedostatochnosti / Ryabov G.А., Аzizov Yu.М. // Аnesteziologia I reanimatologia. – 2008. - №1. – S. 8-13. I.N. Yakovenko. The synthesis and investigation of vasoactive properties of new phosphorylated peptidomimetics / I.N. Yakovenko, O.I. Lukashuk, K.M. Kondratyuk, A.V. Golovchenko, V.V. Zhyrnov, V.S. Brovarets // Journal of Organic and Pharmaceutical Chemistry. – 2013. - V. 11, Iss. 3 (43). – Р. 43-50. Doclinichni doslidzhennya likarskih zasobiv (metodichni rekomendacii) / Za red. О.V. Stefanova. – К.: VD «Аvicena», 2002. – 527 s. Blattner R. Experimenti na isolirovannih preparatah gladkih mishts / Blattner R., Klassen H., Denert H. i dr. - М. : Мir, 1983.- 206 s. Lukiantseva G.V. Dinamika sokratitelnoy aktivnosti isolirovannogo kolcevogo preparata aorti kris pod vliyaniem amilina/ Lukiantseva G.V., Sergeev I.U., Pastuhova V.А., Gunina L.M. // Ukrainskiy morfologichniy almanah. – 2013. – Т. 11, №1. - S. 77-78. Paulis L. Regression of L-NAME-induced hypertension: the role of Nitric oxide and endothelium-derived constricting factor / Paulis L., Zicha J., Kunes J. and others // Hipertension research. – 2008. - № 31. – P. 793-803. Moslemi F. Inhibition of Nitric oxide synthase by L-NAME in male rats / Moslemi F., Nematbakhsh M. and others // Intarnational scholarly research notices: Toxicology. – 2013. – V. 2013. – P. 227-232.